Desarrollo de un plan operativo, considerando parámetros de seguridad industrial, para la puesta en marcha y validación de los equipos a escala piloto, presentes en el centro de purificación y refinación de la Universidad de América (2023)
This project is carried out in order to propose an operational and safety plan for the Purification and Refining Center (CEPURE) of the Center for Sustainable Industry Processes (CEPIIS) of the University of America, evaluating from the possible problems that can be generated during the installation, lifting and assembly processes of the units that correspond to CEPURE. In order to identify possible setbacks that may arise, and also prevent the occurrence of these events, generating a response system according to the situation that arises. With the aim of carrying out the start-up and validation of the equipment in a planned manner, taking into account the particularities and specific precautions that must be taken on each of the units and, in this way, guarantee the correct performance and operation, structurally and internally.